Effects of Topical Icing on Inflammation, Angiogenesis, Revascularization, and Myofiber Regeneration in Skeletal Muscle Following Contusion Injury - Singh, Daniel P.; Barani Lonbani, Zohreh; Woodruff, Maria A.; Parker, Tony J.; Steck, Roland; Peake, Jonathan M. (Frontiers in Physiology, 2017)
Contusion injuries in skeletal muscle commonly occur in contact sport and vehicular and industrial workplace accidents. Icing has traditionally been used to treat such injuries under the premise that it alleviates pain, reduces tissue metabolism, and modifies vascular responses to decrease swelling. Previous research has examined the effects of icing on inflammation and microcirculatory dynamics following muscle injury. However, whether icing influences angiogenesis, collateral vessel growth, and or myofiber regeneration remains unknown. We compared the effects of icing versus a sham treatment on the presence of neutrophils, and macrophages; expression of CD34, von Willebrands factor (vWF), vascular endothelial growth factor (VEGF), and nestin; vessel volume; capillary density; and myofiber regeneration in skeletal after muscle contusion injury in rats. Muscle tissue was collected 1, 3, 7, and 28 d after injury. Compared with uninjured rats, muscles in rats that sustained the contusion injury exhibited major necrosis, inflammation, and increased expression of CD34, vWF, VEGF, and nestin. Compared with the sham treatment, icing attenuated and/or delayed neutrophil and macrophage infiltration; the expression of vWF, VEGF, and nestin; and the change in vessel volume within muscle in the first 7 d after injury (P < 0.05). By contrast, icing did not influence capillary density in muscle 28 d after injury (P = 0.59). The percentage of immature myofibers relative to the total number of fibers was greater in the icing group than in the sham group 28 d after injury (P=0.026), but myofiber cross-sectional area did not differ between groups after 7 d (P = 0.35) and 28 d (P = 0.30). In conclusion, although icing disrupted inflammation and some aspects of angiogenesis/revascularization, these effects did not result in substantial differences in capillary density or muscle growth.